Tree-based farming: A success story of a farmer in Bundelkhand - singh, priyanka; S, Suresh Ramanan; A Arunachalam; R P Dwivedi; Sushil Kumar; Asha Ram; A K Handa (Indian Journal of Agroforestry, 2023)
A progressive farmer, Shri Balakdas Rajpoot from the typical semi-arid Bundelkhand region of Uttar Pradesh has been involved in tree-based farming for more than two decades with the consultation and technical support of ICAR-CAFRI, Jhansi. He has been able to transform and utilize the degraded and unproductive land by planting 200 different tree species and herbs on his farm. ICAR-CAFRI provided him hands-on training in ber grafting and pruning as well as top working of Karonda. With such technical backstopping, the farmer is getting an annual monetary benefit of more than 1 lakh rupees from tree component alone. With greater enthusiasm, the farmer is promoting agroforestry in the region by also distributing tree saplings and imparting training on ber grafting and top working of karonda to fellow farmers in the region. His untiring efforts and achievements by adopting tree-based farming deserved this documentation for greater societal outreach to boost agroforestry in the region. It is believed that such documentation shall help the policy planners and concerned stakeholders to devise suitable programme/projects for promoting agroforestry based sustainable production systems in the semi-arid tropics such as in Bundelkhand.